Pengaruh Pemberian Biokompos Hasil Fermentasi Jamur Trichoderma SPP. Terhadap Pertumbuhan Beberapa Varietas Kedelai (Glycine Max L.) di Lahan Kering - Suhaili Suhaili; Ida Wahyuni (JURNAL AGROPLASMA, 2023)
This study aims to determine the growth response of several soybean varieties on dry land by administering biocompass from the fermented fungus Trichoderma spp to determine the extent of the effect of biocompost fertilizer on the growth of several soybean varieties on dry land. The method used in this study is an experimental method, namely the research is carried out by manipulating the object of research and the presence of controls. The research was carried out on dry land in Giri Tembesi Village, Gerung District, West Lombok Regency, the soil type where the experiment was regusol soil with a pH of 5.7 and a moisture content of 0.77% organic matter. The results showed that the application of biocompost from the fermentation of Trichoderma spp. to some soybean varieties have not been able to stimulate plant growth but in general can adapt to dry land. Differences in soybean varieties resulted in significantly different growth responses. There is no significant difference in the application of biocompost to the growth of soybeans on dry land due to the application dose that is not optimal, so it is necessary to study the optimal dosage of using biocompost. Keywords: Biocompost; dry land; Soya bean; Trichoderma SPP